2000
DOI: 10.1002/1097-0126(200007)49:7<763::aid-pi452>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of fluorocarbon-modified poly(N-isopropylacrylamide)

Abstract: Poly(N‐isopropylacrylamide) copolymers (PNIPAMs) containing pendent perfluoroalkyl (RF) or dodecyl groups have been synthesized by copolymerization of NIPAM with small amounts of RR‐acrylates or ‐methacrylates containing a sulfonamido moiety between the acrylate and RF groups or with dodecyl acrylate. Evidence for strong intermolecular hydrophobic association of the fluorocarbon groups is provided by large viscosity increases with copolymer concentration and upon addition of NaCl and surfactants. These interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Poly( N -isopropylacrylamide) (PNIPAM) is a thermally sensitive polymer with a low critical solution temperature (LCST) of ∼32 °C; namely, it is hydrophilic and soluble in water at temperatures lower than 32 °C but becomes hydrophobic and insoluble at higher temperatures. The incorporation of PFEMAA into PNIPAM enables us to adjust the average interdistance between ferrocene groups by a simple temperature variation. All three copolymers were soluble in water at room temperature because of a low content of PFEMAA.…”
Section: Resultsmentioning
confidence: 99%
“…Poly( N -isopropylacrylamide) (PNIPAM) is a thermally sensitive polymer with a low critical solution temperature (LCST) of ∼32 °C; namely, it is hydrophilic and soluble in water at temperatures lower than 32 °C but becomes hydrophobic and insoluble at higher temperatures. The incorporation of PFEMAA into PNIPAM enables us to adjust the average interdistance between ferrocene groups by a simple temperature variation. All three copolymers were soluble in water at room temperature because of a low content of PFEMAA.…”
Section: Resultsmentioning
confidence: 99%
“…Interest raised by fluorocarbon APs comes from the low surface energy and hydrophobic properties of fluorinated substituents but also from the considerably enhanced viscosifying properties . The degree of substitution has to stay low (a few units per chain) in order to maintain solubility of fluorinated APs in water. , Among the various classes of APs, hydrophobically end-capped poly(ethylene oxide) (PEO) present a well-defined architecture. Because of the known position of hydrophobic groups at each end of the polymer chain, these telechelic APs can be used as model systems for fundamental and systematic studies …”
Section: Introductionmentioning
confidence: 99%
“…Core‐shell microgels of PNIPAAm/poly(viny alcohol) were synthesized and characterized by zeta potential, scanning electron microscopy (SEM), transmission electron microscopy (TEM), nuclear magnetic resonance spectroscopy (NMR), and turbidity measurements 10. Other authors also reported about the synthesis and characterizations of PNIPAAm 11–25. By thorough literature survey, we could not find any report based on the copolymerization of vinyl functionalized nanomaterials like Au and multiwall carbon nanotube (MWCNT) with N ‐isopropylacrylamide (NIPAAm) in the presence of peroxydisulphate (PDS) as a free radical initiator.…”
Section: Introductionmentioning
confidence: 99%